(untitled) (Journal of the College of Education for Women, 2019)
Perhaps one of the most pillars in building communities, and to achieve consistency between its members, is the volunteer work, he is a humanitarian exercise been closely associated with all the meanings of goodness and righteousness since ancient times, but it differs in size and shape and motivations and trends from one community to another, and from time to time; while at least in the stages of calm and stability, it increases in disasters and calamities and wars times, and perhaps (the popular crowd) is the best proof of that, they answered a call reference, and volunteered to defend their land and their holy places. In terms of form it may be donating money or effort or profession or otherwise, either in terms of the trend may be directed from the state and its institutions, or they may be automatic, but the motives are many: psychological, social, political, religious and otherwise.Through the resources and information that reported them in the writing of this research, I found that there is a difference between voluntary behavior, and volunteer work; behavior is voluntary is a behavior group exercised by the individual and to which they apply volunteer work conditions, which comes in response to an emergency circumstance or humanitarian stance; such as saving a drowning or ambulance wounded, or other humanitarian actions pure. The act is the one who does not come at the emergency things but as a result think and ponder, and faith in humanity ideas Semitic, so that translates into charitable acts, and then can this act turns into a social behavior, which may be more advanced Viusa at the level of multiple institutions and organizations that contribute to the collection social efforts and energies, which makes them an active partner for governments in the field of social development.And even achieved a culture of volunteerism in our Arab societies, Iraqi society in particular, there is a need to revitalize the culture of volunteerism on both theoretical Altoesela, and practical application, otherwise it will not be for the Arabs role in this global field, and our culture in this area will be according to the letter of the culture of the western volunteer, on Although this culture is Islamic, Arab in origin. The advanced level reached by the Western society in the field of volunteer work, despite the fact that some of the motives of charitable and voluntary organizations in the West tainted motives of self-interest or political, but some is due to the level of community awareness of the importance of volunteer work, and it was us rather - shall we - be proactive so; being one of the true teachings of the religion of Islam; therefore it is necessary to guide the community awareness of the need and importance of volunteering in the human resources and energy development, and this can be achieved, including the following:- Raising children sound social upbringing, for the purpose of sacrifice and altruistic values, the spirit of teamwork in the hearts of emerging since childhood. - Containment of academic programs and curricula of various educational institutions, some of the courses that are based on the concepts of collective voluntary work, and its importance, combined with practical programs such as clean-up campaigns, and service environment and so on.- Support institutions or bodies working in the field of voluntary work, materially and morally. - To organize training courses for volunteers who are interested in volunteering or by assigning them tasks which volunteer to give them the appropriate skills and experience.- Various media claim more influential role in the definition of what the volunteer work and the need for society to it because of its role in development, and give workers the self-respect and respect for others.- Make volunteering a way to address the behavioral deviation of some of the unemployed. - Use of modern technology in this field in coordination between governmental and non-governmental agencies; to provide social services and the exploitation of human energies.